Inside Cover: Aerobic Toluene Oxidation Catalyzed by Subnano Metal Particles (Angew. Chem. Int. Ed. 4/2019). Issue 4 (20th December 2018) - Huda, Miftakhul; Minamisawa, Keigo; Tsukamoto, Takamasa; Tanabe, Makoto; Yamamoto, Kimihisa
Abstract : Sub‐nanoscale metal particles play critical roles in catalysis for aerobic toluene oxidation. Multiple types of sub‐nanoscale catalytic particles composed of noble metals were created by using dendrimers, which are tree‐like spherical macromolecules that can be used as a template with finely tuned sizes. As described by M. Tanabe, K. Yamamoto, and co‐workers in their Communication onpage 1002 ff., the Pt19 catalyst outperformed a commercial Pt/C catalyst by a factor of 1700 in toluene oxidation.